The Role of Psychological Resilience in Athletic Injury Recovery and Performance - Kaza Mojtahe; Kyle Burrichter, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The essential aim of this research study is to determine the role of psychological resilience in athletic injury recovery also that performance. This research study is based on the primary data analysis for measuring the research study using questions wise data and measuring the analysis through smart PLS software and generating informative results. The descriptive statistic analysis, the indicator correlation, the significant analysis, and the co-linearity statistic analysis between them. The result also presents that smart PLS Algorithm model between dependent and independent variables. Psychological resilience is the main independent and, injury recovery shows a mediator role, and performance is the main dependent variable. The findings of this research contribute to a deeper understanding of the multifaceted nature of cerebral adaptability in the environment of athletic injury recovery and performance. It's hoped that this knowledge informs the development of effective interventions and strategies to enhance cerebral adaptability in athletes, eventually leading to bettered recovery issues and long-term success in sports. The overall research study found positive and significant links between psychological resilience and injury recovery and performance.